2013
DOI: 10.1007/s10534-013-9656-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mercury vapor toxicity by combining deferasirox and deferiprone in rats

Abstract: The hypothesis that combination of deferasirox and deferiprone chelators might be more efficient as combined therapy than single therapy in removing mercury from the body was considered. Male Wistar rats were exposed to mercury vapor for 2 weeks. After mercury administration some abnormal clinical signs such as red staining around the eyes, greenish mottling on the liver, weakness, loss of hair and weight, were observed in animals. Chelators were given orally after mercury vapor application for 2 weeks. Mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…There has also been research to investigate untested chelators for their effectiveness against mercury. For instance, deferasirox and deferiprone were combined and tested on rats [74]. It was observed that this combination was able to successfully chelate mercury and reduced toxic effects of mercury [74].…”
Section: Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been research to investigate untested chelators for their effectiveness against mercury. For instance, deferasirox and deferiprone were combined and tested on rats [74]. It was observed that this combination was able to successfully chelate mercury and reduced toxic effects of mercury [74].…”
Section: Mercurymentioning
confidence: 99%
“…For instance, deferasirox and deferiprone were combined and tested on rats [74]. It was observed that this combination was able to successfully chelate mercury and reduced toxic effects of mercury [74]. One unique experimental chelator was thiol-modified nanoporous Heavy Metals and Cancer http://dx.doi.org/10.5772/intechopen.70348 silica material [75].…”
Section: Mercurymentioning
confidence: 99%
“…Mercury (Hg) is a critical environmental contaminant that exists in liquid form at room temperature. Having been absorbed, Hg is transported via the bloodstream to the organs, where it accumulates in various tissues . Hg accumulation then induces production of reactive oxygen species (ROS) and so generates toxicity in the body .…”
Section: Introductionmentioning
confidence: 99%
“…Having been absorbed, Hg is transported via the bloodstream to the organs, where it accumulates in various tissues. 1,2 Hg accumulation then induces production of reactive oxygen species (ROS) and so generates toxicity in the body. [3][4][5] Accumulation of Hg can happen in any part of the reproductive system such as the corpora lutea and ovaries, and toxicity may develop in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Hg is lipophilic and is absorbed easily by the oral mucosa, skin and lungs. After entering the blood, mercury vapor is oxidized to toxic divalent inorganic Hg (Clarkson 1997), which accumulates in various tissues (Björkman et al 2007, Iranmanesh et al 2013, Yasutake et al 2010. Divalent inorganic Hg stimulates production of reactive oxygen species (ROS) and ROS reduce the level of antioxidant enzymes (Goering et al 2002, Zhao et al 2009.…”
mentioning
confidence: 99%